2011
DOI: 10.3389/fnint.2011.00056
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Temporal Risk Assessment

Abstract: Time is an essential feature of most decisions, because the reward earned from decisions frequently depends on the temporal statistics of the environment (e.g., on whether decisions must be made under deadlines). Accordingly, evolution appears to have favored a mechanism that predicts intervals in the seconds to minutes range with high accuracy on average, but significant variability from trial to trial. Importantly, the subjective sense of time that results is sufficiently imprecise that maximizing rewards in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 78 publications
8
81
0
Order By: Relevance
“…Our findings showed that animals can optimize the number of responses by integrating their numerosity-related uncertainty into their decisions and maximize the reward-rate attained in this task. These findings are consistent with the conclusions of previous studies that utilized temporal decision-making tasks; these studies showed that humans and other animals can adopt reward maximizing temporal decision strategies by taking account of their scalar endogenous timing uncertainty (Balcı et al, 2011;Çavdaroğlu et al, 2014). Thus, this study extended the scope of optimal temporal risk assessment to the domain of numerosity-based decision-making.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings showed that animals can optimize the number of responses by integrating their numerosity-related uncertainty into their decisions and maximize the reward-rate attained in this task. These findings are consistent with the conclusions of previous studies that utilized temporal decision-making tasks; these studies showed that humans and other animals can adopt reward maximizing temporal decision strategies by taking account of their scalar endogenous timing uncertainty (Balcı et al, 2011;Çavdaroğlu et al, 2014). Thus, this study extended the scope of optimal temporal risk assessment to the domain of numerosity-based decision-making.…”
Section: Discussionsupporting
confidence: 91%
“…Reward-rate maximization in this task requires animals to aim at waiting longer than the minimum delay and how much more than the minimum delay animals should on average wait depends on their level of scalar endogenous timing uncertainty. Our previous findings showed that humans and non-human animals can optimize their wait time and maximize the reward-rate (Balcı et al, 2011;Çavdaroğlu et al, 2014; but see Freestone et al, 2015). The results of the current study showed that similar optimal decision-strategies can be attained when the reinforcement schedule is based on the number of responses rather than their timing.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Findings from earlier studies that adopted such an analytical approach [8][9][10][11][12] showed that both humans and rodents can adopt nearly optimal strategies by taking account of their endogenous uncertainty in tasks that required various decisions. In one of these experiments [8], humans and mice were trained in a temporal discrimination task that was composed of two types of trials (short latency trial and long latency trial) presented probabilistically.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant timed behaviors have been shown to be sensitive to other crucial elements of environmental statistics, such as the probabilities of different outcomes (2)(3)(4). However, how steady-state choice behavior emerges in temporal decision-making tasks that contain probabilistic contingencies remains to be answered.…”
mentioning
confidence: 99%